The How Matters: How Primary Care Provider Communication With Team Relates to Patients' Disease Management. Issue 7 (July 2020) - Lee, Yuna S.H.; King, Marissa D.; Anderson, Daren; Cleary, Paul D.; Nembhard, Ingrid M.
Abstract : Background: Investigating primary care provider (PCP)-team communication can provide insight into how colleagues work together to become high-functioning teams more able to address an increasingly complex set of tasks associated with chronic disease management. Objective: To assess how PCP communication with their care team relates to patients' health. Research Design: Longitudinal study of how 3 aspects of PCP-care team communication—participation, time spent listening, and uninterrupted speaking length—relate to disease management of patients with hypertension or diabetes, and the effect of these team communication behaviors on PCP-patient communication as a pathway by which this relationship might exist. We used multilevel regression models. Subjects: Twenty-seven PCPs and 98 team members, and 18, 067 patients with hypertension and 8354 patients with diabetes affiliated with a federally qualified health center with 12 practice sites. Measures: Primary data on communication collected using sociometric sensors worn by PCPs and team members, patient-PCP communication data collected with surveys, and patient health, PCP and patient characteristics extracted from electronic records. Results: PCPs participated in 75% of care team conversations, spent 56% of conversation time listening, and had an average uninterrupted speaking length of 2.42 seconds. PCP participation, listening, and length of uninterrupted speaking time were associated with significantly higher odds that their patients had controlled hypertension and diabetes and improvements in disease control over time. PCP-patient communication mediates this relationship. Conclusions: PCP-team communication is associated with patient health management. How team members speak with one another may be as important as the content of their communication.